Bacterial growth and ceftriaxone activity in individual ascitic fluids in an in vitro model of spontaneous bacterial peritonitis - van Os, Wisse; Wulkersdorfer, Beatrix; Eberl, Sabine; Oesterreicher, Zoe; Schwabl, Philipp; Reiberger, Thomas; Paternostro, Rafael; Weber, Maria; Willinger, Birgit; Zeitlinger, Markus (Frontiers in Pharmacology, 2023)
Introduction: The infection site environment affects bacterial growth and antibiotic activity. When bacterial growth and kill are studied in body fluids, samples of multiple subjects are usually pooled, averaging potentially relevant differences in composition. The ascitic fluid (AF) environment is frequently associated with spontaneous bacterial peritonitis (SBP) in cirrhotic patients. In this study, bacterial growth and ceftriaxone activity were evaluated in individual AF using an in vitro model of SBP, reflecting the environment and pharmacokinetics at the infection site. Methods: AF was obtained from nine cirrhotic patients with non-infected ascites. Growth of nine bacterial strains (three Escherichia coli, four Staphylococcus aureus, one Enterococcus faecalis, and one Klebsiella pneumoniae) in individual AF was assessed and correlated with biomarkers including potential risk factors for SBP. Ceftriaxone time-kill experiments, in which the pharmacokinetic profile observed in AF following a 1 g intravenous infusion was replicated, were performed with two E. coli and two S. aureus isolates with minimum inhibitory concentrations around the ceftriaxone resistance breakpoint. Results: High variability in growth between strains and AF of different patients was observed. More favourable conditions for bacterial growth were observed in AF of patients with lower protein, albumin and complement C3c levels in AF and higher serum bilirubin and alanine aminotransferase levels. Ceftriaxone was active in AF, even against resistant isolates. Conclusions: Ascites patients may be predisposed to or protected against SBP based on the antimicrobial capacity of their AF. Ceftriaxone at clinical AF concentrations is active in the AF environment.